South Sudanese Women in Cairo: The Making and Re-making of Life under Precarious Conditions - Abdulhak, Nour (AUC Knowledge Fountain, 2021)
This thesis discusses how South Sudanese women mobile subjects who choose domestic work as a livelihood navigate life in the city of Cairo. The thesis unpacks how these women’s precarious conditions and different individual and structural factors or policies affect the way they make and re-make their lives in Cairo. While it is common for South Sudanese women to do domestic work in Egypt, this population has been neglected by academia and policy makers. Due to the academic limitations on this topic, interviews with experts were conducted alongside the ethnographic study of these women’s lives to attain the closest depiction of reality. For most participants in this ethnographic study, Egypt was considered to be a transit location where they see themselves stuck, waiting for any change to move on. I use the term transit as their lives in Egypt are continuously impacted by various factors that eventually lead them to desire to move onwards to a third country in the Global North, or return to South Sudan. This thesis is based on in-depth interviews, mainly with South Sudanese migrant domestic workers living in Cairo. I investigated why most South Sudanese women chose to undertake domestic work as an occupation rather than pursue other types of work in the formal or informal sectors. Other data sources included were demographic and statistical data, relevant work of other researchers in the field, and field visits and interviews with different stakeholders such as employers, migration experts, and domestic work agencies. Field research examined the infrastructure available to these women as they navigate their livelihoods, focusing specifically on how they enter the labor market. The thesis also explores how these women variously find a foothold in Egypt and interact with the different transnational networks and communities upon arrival, and how gender dynamics change within the context of displacement. This study refers to Egypt as a transit country from which the potential for onward migration is significant, and as all the women I interviewed chose to either move onwards or return to South Sudan. None chose to stay in Egypt due to harassment and racism, restrictive policies on work, education, citizenship and residency, lack of police protection, and lack of a prosperous future.